Blogs and the Legal Academy - Orin S. Kerr (Washington University Law Review, 2006)
This paper's focus is on today’s technology and ask whether blogs as we know them today are conducive to advancing scholarship. This paper's conclusion is that relative to other forms of communication, blogs do not provide a particularly good platform for advancing serious legal scholarship. The blog format focuses reader attention on recent thoughts rather than deep ones. The tyranny of reverse chronological order limits the scholarly usefulness of blogs by leading the reader to the latest instead of the best. This doesn’t mean that blogs can’t advance scholarship. The impact of any blog depends on what its author decides to post. But the format of blogs makes it relatively hard to sustain a deep conversation about an important legal issue. As a result, blogs can play an important role in the dissemination and critique of scholarship, but, on the whole, they tend to provide lighter fare than other media. This paper suggests that blogs will probably have the greatest impact on legal scholarship at the student level: student scholarship published in law reviews has often focused on recent developments, and blogs may eventually usurp that role. This paper's second point is that blogs provide a promising platform for law professors interested in being public intellectuals. Law professor blogs allow professors to participate in and influence broader debates on lawrelated topics. This role isn’t new, but it’s an interesting new spin on an old role. Blog posts have some important advantages over more traditional forms of public speech, such as op-eds, magazine articles, and TV or radio appearances. The opportunities aren’t specific to law professors, of course. Anyone can start a blog, and anyone can use a blog to become a public intellectual. But the legal field is particularly conducive to this kind of role, and law professors are in a good position to take advantage of it.
Keywords: Law -- Study & teaching; Blogs; Legal education; Legal literature; United States